Ablating the Posterior Heart: Cardioesophageal Fistula Complicating Radiofrequency Ablation in the Coronary Sinus. (12th October 2015) - GÜNEŞ, MAHMUT FATIH; GÖKOĞLAN, YALÇIN; DI BIASE, LUIGI; GIANNI, CAROLA; MOHANTY, SANGHAMITRA; HORTON, RODNEY; BAILEY, SHANE; NATALE, ANDREA
Ablating the Posterior Heart: Cardioesophageal fistulas (CEFs) are uncommon but life‐threatening complications of radiofrequency (RF) catheter ablation of atrial fibrillation (AF). They are usually, but not exclusively, related to ablation of the left atrial posterior wall. We report a case of a 73‐year‐old man that presented with CEF following RF ablation in the coronary sinus, highlighting the importance of esophageal temperature monitoring whenever ablating in the posterior heart.